PENGETAHUAN PERAWAT TENTANG PENATALAKSANAAN LUKA KRONIK DENGAN KONSEP LEMBAB DI RUMAH SAKIT REKSA WALUYA MOJOKERTO - Vonny Nurmaleya Megawati (Wiraraja Medika : Jurnal Kesehatan, 2015)
Today wound care method, tend to use gauze dressing method "wet-to-dry". When themoist gauze become dry, it will hit the surface of the tissue.The result not only affected tissuegrowth, but also cause a pain. The purpose of wound care is making a conduciveenvironment for the tissue that support the process of wound healing. For that developed awound care method by keeping the environment moist. Therefore this study was conductedto identify nursing knowledge about the management of chronic wounds in hospital ReksaWaluya.This study uses a descriptive design. Variables investigated included nurse knowledgeabout the treatment of chronic wounds with moist concept. The samples of this study are 23vocasional nurse in Reksa Waluya Hospital by using simple random sampling technique. Theresearch instrument was a questionnaire. The results of this study are presented in the formof frequency distribution tables, with a good knowledge of criteria, sufficient and less.The results showed that the nurse knowledge about the treatment of chronic woundswith moist concept in the Reksa Waluya hospital, more than 50% of respondents had enoughknowledge as many as 15 people (55.6%), while a small portion of respondents lessknowledge about the management of chronic wounds with the moist concept is as much astwo persons (7.4%).Nurses knowledge enough about the concept of moist wound care so that nurses did notknow about the benefits and purpose of the treatment of chronic wounds with the moistconcept. In the application in a hospital the nurse haven’t apply the moist concept to treat thechronic wounds but still using wet to dry wound care method. Nursing knowledge aboutchronic wounds management in Reksa Waluya hospital should be improved. This can bedone by following a training or seminar on treatment of chronic wounds with the concept ofmoist. With the purposeof improving service and patient satisfaction.Key words : Knowledge, chronic, moist wound care.